Tema Cerpen Dalam Majalah Al-Hikmah: satu analisa (1hb. April 1934 - 15hb. Disember 1941) - Yusoff, Mohammed (Universiti Sains Malaysia, 1978)
This analysis is based on the themes of the shortstories published in Al-Hikmah from 1st. April 1934 until 15￡h. December 1941. The themes are divided into several aspects to enable the researcher to analyse them in detail. A systematic study of the development of each theme, is then considered for such an approach would certainly help to ascertain whether the themes actually reflect the true picture of the social development at the time when the stories were written.